A parametric study of residual stress in plate - S. Agrawal, Nikhil; B. Kulkarni, P; D. Pachpor, P; N. Khapre, R; Nakhate, Dipak (International Journal of Engineering and Technology, 2018)
Residual stress is a process-induced stress in a molded part that exists in the body in the absence of external loading or it exists in steel section of the unloaded state. Residual stress is also termed as ‘Locked Stress’. This paper presents to find out this lock stress analytically. The theoretical and analytical inputs are considered in terms of aspect ratio and these results are compared by percentage error. The previous study mentioned many experimental methods by which residual stresses were sorted out. A Plate is a flat surface having thickness small as compared to other two dimensions. Researchers are mainly focused on the treatment of the different plate theories related to Kirchhoff or Reissner/Mindlin. The developed ANSYS finite element model analyzed square and rectangular plate and compared the analytical results in terms of deflection and stress with theoretical results which are obtained from classical theory. Different boundary conditions for different plate size are considered and solved.